VISUAL ACUITY AND CLINICAL REFRACTION FOLLOWING IMPLANTATION OF VARIOUS MULTIFOCAL INTRAOCULAR LENSES - N. N. Temirov; N. E. Temirov (Oftalʹmologiâ, 2015)
Aim. To analyze visual acuity, clinical refraction, and defocusing tolerance after the implantation of monofocal IOL with rotational asymmetric optic (Lentis Mplus 313 MF) compared with Acrysof ReSTOR SN6AD1.Materials and methods. Phacoemulsification was performed in a total of 194 patients (288 eyes), i.e., 144 patients (188 eyes) with cataract and 50 patients (100 eyes) with presbyopia and high ametropia. The patients were divided into two groups. Study group included 132 patients (194 eyes) implanted with Lentis Mplus while control group included 62 patients (94 eyes) implanted with Acrysof ReSTOR. Uncorrected distance (5 m), intermediate (50‑70 cm), and near (20‑40 cm) visual acuity under photopic (85 cd/m2) and mesopic (8 cd/m2) conditions were measured, objective and subjective refractometry were performed, and defocusing tolerance was evaluated.Results. Postoperatively, uncorrected distance and near visual acuity was high while intermediate visual acuity was moderately low. Lentis Mplus patients had better near and intermediate visual acuity under mesopic conditions as compared with Acrysof ReSTOR patients. Emmetropia (target refraction) was achieved in 90.2% of study group patients and in 87.2% of control group patients. In patients implanted with Lentis Mplus, refraction was measured by subjective method. Optimal A-constant for Lentis Mplus and Acrysof ReSTOR was 118.0 and 118.6, respectively. Under defocusing, Lentis Mplus patients had better visual acuity than Acrysof ReSTOR patients. This indirectly confirms better intermediate vision.Conclusions. Lentis Mplus provides better vision at various distances that does not almost depend on light levels and induces minimal dysphotopsia.